Cover Picture: Tiara[5]arenes: Synthesis, Solid‐State Conformational Studies, Host–Guest Properties, and Application as Nonporous Adaptive Crystals (Angew. Chem. Int. Ed. 10/2020). Issue 10 (27th January 2020) - Yang, Weiwei; Samanta, Kushal; Wan, Xintong; Thikekar, Tushar Ulhas; Chao, Yang; Li, Shunshun; Du, Ke; Xu, Jun; Gao, Yan; Zuilhof, Han; Sue, Andrew C.‐H.
Abstract : Tiara[5]arenes, five‐fold‐symmetric macrocycles consisting of phenolic units linked by para ‐substituted methylene bridges, were synthesized by H. Zuilhof, A. C.‐H. Sue, and co‐workers. In their Research Article on page 3994, the construction and derivatization are demonstrated, along with solid‐state structures, host–guest properties in solution, and application as nonporous adaptive crystals for the separation of benzene and cyclohexane.